Assessing Resilience and Sustainability of the Mississippi River Delta as a Coupled Natural-Human System - Xu, Y. Jun; Lam, Nina S.-N.; Liu, Kam-biu (Water, 2018)
This book contains 14 articles selected from a special issue on the assessment of resilience and sustainability of the Mississippi River Delta as a coupled natural-human system. This effort is supported in part by a U. S. National Science Foundation grant. The goal of this book is to present some of the recent advances in research and research methodologies, major discoveries, and new understanding of the Mississippi River Delta, which represents one of the most challenging cases in finding the pathways for coastal resilience and sustainability because of the complexity of environmental and socioeconomic interactions. The articles are contributed by 39 researchers and they studied the deltaic system from five aspects including 1) riverine processes and sediment availability, 2) sediment deposition and land creation, 3) wetland loss, saltwater intrusion, and subsidence, 4) community resilience and planning, and 5) review and synthesis. As editors, by reviewing and putting these papers together, we have realized a major challenge in conducting an interdisciplinary assessment of resilience: How to identify a “Common Threshold” from different scientific disciplines for a highly nature-human intertwined river delta system? For instance, the threshold for sustaining a river delta in the view of physical sciences is different from that of social sciences. Such a common threshold would be a radical change and/or a collapse of a coupled natural-human delta system if nothing can be or will be done. Identifying the common threshold would help guide assessment and evaluation of the resilience of a CNH system as well as the feasibility and willingness of protecting the system’s resilience. We hope this book will be a first step toward inspiring researchers from different disciplines to work closely together to solve real problems in sustaining precious river delta ecosystems across the globe.
Keywords: Gulf of Mexico; Mississippi River Delta; coupled natural-human system (CNH); resilience; river deltas; sustainability